Determinan Kinerja Perbankan Syariah - Munawarah .; Sarmiana Batubara; Ratna Sari Dewi (AGHNIYA : Jurnal Ekonomi Islam, 2020)
This study aims to see the effect of size, capitalization, risk and inflation affect ROE. This research is a quantitative research. The population used in this study is Islamic banking in Indonesia. The sample used is Islamic banking registered with OJK and BI which publish their financial reports in a row from 2015 to 2017 and have the data needed in this study. Based on the results of the study showed that partial size, capitalization, and inflation had no significant effect on ROE, while the risk variable had a significant effect. This research also shows that simultaneous size, capitalization, risk and inflation have a significant effect.